Odpowiedź:
Obliczamy q
[tex]a_6 \cdot q^3 = a_9\\\\\frac{a_6}{a_9} = \frac{a_6}{a_6\cdot q^3} = \frac{1}{q^3} = 2\sqrt{2} \phantom{..} /\cdot q^3\\\\2\sqrt{2} \cdot q^3 = 1 \phantom{..} / : 2\sqrt{2}\\q^3 = \frac{1}{2\sqrt{2}} = (\frac{1}{\sqrt{2}})^3\\\\q = \frac{1}{\sqrt{2}}[/tex]
Na koniec usuwamy niewymierność z mianownika
[tex]q = \frac{1}{\sqrt{2}} \cdot \frac{\sqrt{2}}{\sqrt{2}} = \frac{\sqrt{2}}{2}[/tex]
Mając q obliczamy 10 wyraz
[tex]a_{10} = a_3 \cdot q^7\\a_{10} = 8 \cdot (\frac{\sqrt{2}}{2}})^7 = \frac{64\sqrt{2}}{128} = \frac{\sqrt{2}}{2}[/tex]
Szczegółowe wyjaśnienie: